Multiple skin cancers in patients with mycosis fungoides after long‐term ultraviolet phototherapy. (22nd May 2017) - Imafuku, K.; Hata, H.; Yanagi, T.; Kitamura, S.; Inamura‐Takashima, Y.; Nishimura, M.; Kitamura, S.; Moriwaki, S.; Shimizu, H.
Summary : Phototherapy is a useful noninvasive therapy, but it can induce cutaneous malignant tumours, including squamous cell carcinoma (SCC) and basal cell carcinoma (BCC). We report on a 79‐year‐old man who had long‐standing mycosis fungoides for 40 years, which had been treated with psoralen ultraviolet A therapy for 37 years at a dose of approximately 5000 J/cm 2 . Approximately 6 years before presentation, numerous types of cutaneous malignancies, including actinic keratosis, BCC and SCC, had begun to develop all over the patient's body. We hypothesized that he was experiencing a pathogenesis similar to patients with xeroderma pigmentosum (XP), and we therefore assessed his DNA repair capacity. Based on these investigations, the patient was eventually diagnosed as non‐XP, even though we detected that his DNA repair capacity was slightly lower than that of normal controls, which may have led to the skin cancers. We speculate that multiple skin malignancies can be induced by long‐term phototherapy in patients with slightly impaired DNA repair capacity.